Empathy-Driven Humanization: Employment Instability, Burnout, and Work Engagement Among Temporary Nurses in a Sustainable Workforce Model - Sonia Prieto-de Benito; Carlos Ruíz-Núñez; Juan Pablo Hervás-Pérez; Cayetana Ruíz-Zaldibar; Fidel López-Espuela; Raquel Caballero de la Calle; Ivan Herrera-Peco (Nursing Reports, 2025)
Background/Objectives: Employment instability is increasingly recognized as an organizational stressor, yet its combined effect on nurse burnout, humanized care, and work engagement is poorly quantified. This study investigates those relationships and tests a serial mediation model linking contract instability, burnout, humanization, and engagement in Spanish hospital nurses. Methods: A nationwide cross-sectional survey was completed by 400 fixed-term nurses between March and May 2025. The data included demographics, number of contracts signed during 2024, and scores on the Maslach Burnout Inventory (MBI), Utrecht Work Engagement Scale (UWES), and Health Professionals’ Humanization Scale (HUMAS). Spearman coefficients described the bivariate relations. Results: Burnout correlated positively with both contract count (r = 0.42, p = 0.039) and years of experience (r = 0.74, p = 0.040). Work engagement was inversely associated with instability (r = –0.62, p = 0.018). Humanized care was strongly and negatively related to burnout (r = –0.61, p = 0.032), particularly in sociability and self-efficacy dimensions. Discussion: Contractual precarity elevates burnout, erodes perceptions of humanized care, and, through this erosion, suppresses nurse engagement. Stabilizing workforce arrangements and strengthening empathy-centered skills may mitigate these effects and foster a socially sustainable nursing workforce.